Approach to keyword search over encrypted data in cloud - Peng ZHANG; Yan LI; Hai-lun LIN; Rong YANG; Qing-yun LIU (Tongxin xuebao)
With the advent of cloud computing,large-scale data are being increasingly outsourced to the cloud.For the protection of data privacy,sensitive data has to be encrypted before outsourcing,which makes effective data utilization a very challenging task.Although traditional searchable encryption approaches allow users to search over encrypted data through keywords,they don’t capture any relevance of data files,so users have to spend much time on post-processing every retrieved file in order to find ones most matching their interest.Moreover,retrieving all files containing the queried keyword further incurs unnecessary network traffic,which is not accord with pay-as-you-use cloud paradigm.An approach to ranked keyword search over encrypted data in cloud is proposed.Ranked search greatly mitigate the user’s effort by returning the matching files in a ranked order,and also protects the data privacy by order-preserving encryption.Extensive experimental results demonstrate the efficiency.